2018
DOI: 10.1002/adhm.201800441
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Plotted Beta‐Tricalcium Phosphate Scaffolds with Smaller Pore Sizes Improve In Vivo Bone Regeneration and Biomechanical Properties in a Critical‐Sized Calvarial Defect Rat Model

Abstract: Due to the difficulty in fabricating bioceramic scaffolds with smaller pore sizes by the current 3D printing technique, the effect of smaller pore sizes (below 400 µm) of 3D printed bioceramic scaffolds on the bone regeneration and biomechanical behavior is never studied. Herein beta-tricalcium phosphate (β-TCP) scaffolds with interconnected smaller pores of three different sizes (100, 250, and 400 µm) are fabricated by 3D plotting. The resultant scaffolds are then implanted into rat critical-sized calvarial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…Here, scaf-folds with 0.10 mm channels performed better than more open channels. 94 Because the defect only had a depth of 0.5 mm, the animal study design might have favored the smaller channels.…”
Section: Osteoconduction and Microarchitectures Derived From Additivementioning
confidence: 99%
“…Here, scaf-folds with 0.10 mm channels performed better than more open channels. 94 Because the defect only had a depth of 0.5 mm, the animal study design might have favored the smaller channels.…”
Section: Osteoconduction and Microarchitectures Derived From Additivementioning
confidence: 99%
“…In the process of bone tissue repair, 3D interconnected macropore structures of the scaffolds are necessary for the delivery of nutrients and metabolic wastes, and is beneficial for cell growth and migration. We first prepared HA powder to develop a homogeneous paste with appropriate viscosity, and then fabricated the 3D-plotted HA porous scaffold with interconnected macropore structures [ 18 , 27 ]. As shown in Figure S1 , HA scaffolds with various structures (such as shape, size, and pore structure) were fabricated by 3D plotting.…”
Section: Resultsmentioning
confidence: 99%
“…For the application of bioceramic in bone tissue engineering, most studies have focused on controlling the crystal size [ 17 ], pore size [ 18 , 19 ], pore structure [ 5 , 20 ], porosity [ 21 , 22 ], and surface topography [ 23 , 24 ]. It was confirmed that bioceramic scaffolds with pore sizes > 200 µm are necessary to enhance bone formation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al (Chang et al, 2000) reported bone ingrowth in the porous HAp implants with different pore sizes (50, 100, 300, and 500 μm) in the proximal tibia of rabbits and concluded that the 300-μm sized pores in the HAp implants were optimum. Diao et al (2018) by cell-cell contact. Moreover, infiltration of capillaries was observed in the porous HAp blocks with pore sizes more than 300 μm.…”
Section: Discussionmentioning
confidence: 99%
“…Taking these reports into consideration, a pore size ranging from 300 to 400 μm seems to be optimal for porous HAp. Diao et al (2018) by cell-cell contact. In short, smaller pore size provides narrower space for colonization and increases the opportunities for cell-cell contact, which facilitates osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%